Health Potential of Aloe vera against Oxidative Stress Induced Corneal Damage: An "In Vitro" Study - Ida Ceravolo; Federica Mannino; Natasha Irrera; Francesco Squadrito; Domenica Altavilla; Giorgia Ceravolo; Giovanni Pallio; Letteria Minutoli (MDPI AG, 2021)
Fuchs endothelial corneal dystrophy (FECD) is characterized by the gradual deterioration of corneal endothelial cells (CECs) and is the most common cause of corneal transplantation worldwide. CECs apoptosis caused by oxidative stress plays a pivotal role in the pathogenesis of FECD. Antioxidant compounds have been of considerable significance as a candidate treatment in the management of corneal diseases. Based on these findings, the objective of this study was to evaluate the effects of an aloe extract with antioxidant properties, in an "in vitro" model of FECD. Human corneal epithelial (HCE) cells were preincubated with aloe extract 100 μg/mL, two hours before hydrogen peroxide (H2O2) stimulus. H2O2 challenge significantly reduced the cell viability, increased the generation of Reactive Oxygen Species (ROS) and malondialdehyde levels. Moreover, m-RNA expression and activity of Nrf-2, Catalase and Superoxide dismutase (SOD) were reduced together with an enhanced expression of IL-1β, tumor necrosis factor-α (TNF-α), IL-6, and cyclooxygenase 2 (COX-2). Furthermore, Bcl-2, Caspase-3 and Caspase-8 expression were down-regulated while Bax was up-regulated by H2O2 stimulus. Aloe extract blunted the oxidative stress-induced inflammatory cascade triggered by H2O2 and modulated apoptosis. Aloe extract defends HCE cells from H2O2-induced injury possibly due its antioxidant and anti-inflammatory activity, indicating that eye drops containing aloe extract may be used as an adjunctive treatment for FECD.